Psychogenetic research of intelligence: Methods, problems, and results - Čepas, V. (Psichologija, 1984)
The problem of social and biological in man is one of the central problems of many sciences. In the psychological field the problem is studied by psychogeneticists with the help of twin's method. In this article some information is given about twin's method, its varieties and possibilities in psychological research of intellect (IQ). Attention is given to some urgent problems of studying hereditability of IQ. Psychological research of IQ in the USSR and abroad is analysed. Results achieved when studying monozygotic (MZ) and dizygotic (DZ) twins as well as separated twins (MZ and DZ) and siblings are discussed. A conclusion is drawn that it is impossible to answer single-meaningly the question if intellect is inherited or not. For the further solution of the problem more close cooperation of different sciences is necessary.
Keywords: intelligence; heritability; psychogenetic research; twin’s method